Tindak Tutur Ilokusi dalam Video Podcast Deddy Corbuzier dan Najwa Shihab pada Media Sosial Youtube - Neni Widyawati; Asep Purwo Yudi Utomo (Universitas Muhammadiyah Mataram, 2020)
The background of this study is the description of the illocutionary speech acts in the speech of speaker and hearer. This study aims to describe the illocutionary speech acts in the Deddy Corbuzier and Najwa Shihab video podcasts on YouTube social media. This research is a qualitative descriptive research. The data source of this research is Deddy Corbuzier and Najwa Shihab's podcast videos on YouTube social media published on February 16, 2020. The data in this study are speech transcripts in the form of sentences or paragraphs that indicate illocutionary speech acts in Deddy Corbuzier and Najwa Shihab's social media on youtube social media. Data collection techniques in this research are listening and note taking techniques. The results showed 16 illocutionary speech acts in the Deddy Corbuzier and Najwa Shihab video podcasts on social media youtub with details (a) 8 assertive speeches, (b) 1 directive speech, (c) 2 commissive speeches, (d) 4 expressive speeches, and (e) 1 declarative speech. The illocutionary act that dominates is assertive namely 8 data, both spoken by Najwa Shihab and Deddy Corbuzier, while the least illocutionary acts found are directive and declarative illocution, which are only 1 data each. The benefit of this research is that it can be used as a reference for various language activities.